Application of extended reality in pediatric neurosurgery: A comprehensive review - Yau-Zen Chang; Chieh-Tsai Wu (Biomedical Journal, 2025)
The integration of Extended Reality (XR) technologies, including Augmented Reality (AR) and Virtual Reality (VR), represents a significant advancement in pediatric neurosurgery. These technologies offer immersive and interactive 3D visualization capabilities, which enhance the precision and accuracy of surgical procedures. This comprehensive review systematically examines the current applications of XR in pediatric neurosurgery. The review adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, which provide criteria for reporting systematic reviews and meta-analyses. It also utilizes the PICOS (Population, Intervention, Comparison, Outcome, Study design) framework to formulate research questions and structure literature searches. A thorough search of multiple databases yielded 1434 relevant articles, supplemented by an additional 55 articles obtained through manual searches. The review includes a detailed analysis of the XR workflow, its surgical applications, and associated outcomes. It emphasizes the practical benefits of XR in preoperative planning, intraoperative navigation, and postoperative assessment. Furthermore, the paper discusses the challenges, opportunities, and future prospects of XR in pediatric neurosurgery, including its effects on surgical outcomes, medical education, and patient care. By synthesizing technological developments with clinical applications, this review provides a comprehensive understanding of the multifaceted roles of AR and VR in pediatric neurosurgical practice. It covers innovative methods, applicable scenarios, datasets, and metrics, along with a comparative analysis of state-of-the-art techniques, considering differences in input data. Ultimately, this review aims to present an overview of the current landscape of XR in pediatric neurosurgery to inform future research and clinical practice.